Reti sociali e innovazione I sistemi locali dell'informatica - Ramella, Francesco; TRIGILIA, CARLO (Studi e saggi, 2005)
The lagging behind of the Italian economy in the sphere of technologically advanced manufacture represents a significant factor in the debate on the risks of the country's decline. Nevertheless we know relatively little about the diffusion in Italy of companies specialising in information technology. The research presented in this book - the outcome of a national project - reveals how this sector is dominated by small businesses, concentrated in a number of urban areas (the cases studied are Pisa, Florence, Turin, Osimo and Castelfidardo). It emerges that the social networks linking the businessmen with University researchers are crucial to an understanding of the processes of innovation. But what is equally important is the capacity of the collective entities, both public and private, to provide the entire country with the services that are indispensable for the development of enterprise.